PENGARUH CASH CONVERSION CYCLE, AVERAGE COLLECTION PERIOD, INVENTORY TURNOVER, AVERAGE PAYMENT PERIOD TERHADAP PROFITABILITAS PERUSAHAAN DENGAN CURRENT RATIO DAN SALES GROWTH SEBAGAI VARIABEL KONTROL (Studi pada Perusahaan Manufaktur yang terdaftar di BEI periode 2013-2016) - Octaviani Putri, Silvia Nur; Demi Pengestuti, Irene Rini (Diponegoro Journal of Management, 2018)
Working capital is a part of resources that can have a impact on company’s profitability. The research is aimed at determining the effect of policy of working capital on profitability in manufacturing companies listed on the Indonesian Stock Exchange (IDX). The variables consists of cash conversion cycle (CCC), average collection period in days (ACPID), inventory turnover in days (ITID), average payment period in days (APPID), profitability (ROA).The population of this research consists of 144 manufacturing companies listed on the IDX in years 2013-2016. This research used secondary data and used purposive sampling method in determining the sample. The total sample in this study are 62 companies. Multiple regression is used as the analysis technique in this research.The result of this research that cash conversion cycle (CCC), average collection period in days (ACPID), inventory turnover in days (ITID) have negative significant effect with profitability, moreover average payment period in days (APPID) found has no significant effect on profitability. The coefficient determinant R2 is 0,32 which means 32% ROA variant explained by independent variables, whereas 62% explained by another variables which is not followed.